Efficacy and safety of bromocriptine quick release as an add on therapy with metformin and glipizide in type 2 diabetes mellitus patients: an open label randomized controlled study - M., Nithyapriya; Purushotaman, S. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Type 2 Diabetes Mellitus (DM) is a metabolic disorder, treated by insulin and oral hypoglycaemic agents (OHA). Despite treatment, to protect diabetic population from its complications is difficult. So, there is a need for an OHA with different mechanism of action and minimal side effects. Bromocriptine Mesylate QR (Quick release) formulation was approved by FDA for treatment of type 2 DM. Hence, this study was planned to highlight the usefulness of Bromocriptine QR in type 2 diabetes mellitus. Methods: Total 140 patients with type 2 DM were randomized into two groups. The control group was treated with Metformin 500 mg BD (twice daily) and Glipizide 5 mg BD for a period of 3 months. The study group received Bromocriptine quick release 1.6 mg once daily, metformin 500 mg BD and Glipizide 5 mg BD for a period of 3 months. In both control and study groups, fasting blood glucose, postprandial blood glucose was monitored at 0, 1st, 2nd and 3rd month. HbA1C was done at baseline and at the end of 3 months. Results: There was statistically significant decrease in fasting blood glucose, postprandial blood glucose and HbA1C when compared to baseline in both control group (p <0.05) and study group (p <0.05) at the end of 3 months. But the decrease in FBS, PPBS, HbA1C was higher in the study group (p=0.0001) than the control group (p=0.001). Conclusions: In type 2 DM patients, Bromocriptine QR, combined with metformin and Glipizide reduced fasting and postprandial blood glucose and HbA1C significantly compared to metformin and glipizide alone.